Behavior of Vandalism in Junior High School Students - Husnul Fuadi; Afdal Afdal (Universitas Negeri Padang, 2021)
Behavioral vandalism carried out by students by scribbling learning facilities and infrastructure such as scribbling on walls, doors, tables and chairs using x-tips, pens, markers and pencils.This study aims to determine the description of vandalism behavior of students in junior high schools. This type of research is qualitative research in the form of case studies. The subjects in this study were 3 junior high school students using purposive sampling technique. Data collection instruments used in this study were interview, observation, and documentation guidelines. The data analysis technique used in this research is thematic analysis by conducting transcripts of interviews that have been verbatim The results revealed that all research subjects (vandals) had vandalistic behavior, good, cognitive, affective, psychomotor to the perpetrator of the vandal, the cause of the vandal. Furthermore, the three subjects preferred to close themselves related to their vandal orientation. Two of the three vandals felt less comfortable at home but remained at home alone in their room, while one other felt more comfortable outside the house, and rarely spent time at home so that the communication that occurred in between children and parents is reduced and makes the relationship less close, therefore opening up feels difficult to do.